2020
DOI: 10.3390/ijms21145116
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Kinetics of an Enzymatic Reaction through Enzyme or Substrate Confinement into Lipid Mesophases with Tunable Structural Parameters

Abstract: Lipid liquid crystalline mesophases, resulting from the self-assembly of polymorphic lipids in water, have been widely explored as biocompatible drug delivery systems. In this respect, non-lamellar structures are particularly attractive: they are characterized by complex 3D architectures, with the coexistence of hydrophobic and hydrophilic regions that can conveniently host drugs of different polarities. The fine tunability of the structural parameters is nontrivial, but of paramount relevance, in order to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…For example, Negrini et al established a swollen LCP (SLCP) where aqueous channel sizes ranged from 38.5 to 83.4 Å in diameter and found that the diffusion coefficients of a model polysaccharide (10,000 Da) and gold nanoparticles (2 and 5 nm) were enhanced by swelling the cubic nanostructure. For proteins that have potential medicinal properties, this behavior was also reported in an in meso enzymatic reaction system and an injectable gel system . However, the diffusion of peptides and proteins with various molecular mass and sizes from SLCPs has not been systematically examined.…”
Section: Introductionmentioning
confidence: 90%
“…For example, Negrini et al established a swollen LCP (SLCP) where aqueous channel sizes ranged from 38.5 to 83.4 Å in diameter and found that the diffusion coefficients of a model polysaccharide (10,000 Da) and gold nanoparticles (2 and 5 nm) were enhanced by swelling the cubic nanostructure. For proteins that have potential medicinal properties, this behavior was also reported in an in meso enzymatic reaction system and an injectable gel system . However, the diffusion of peptides and proteins with various molecular mass and sizes from SLCPs has not been systematically examined.…”
Section: Introductionmentioning
confidence: 90%
“…Thematic Area 2 includes 22 articles, namely [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], the typification of which is shown in Table 3 . With some degree of conventionality, it is possible to subdivide the articles published here into two main groups, namely, articles devoted to the study of the kinetics of processes in which any chemical transformations are decisive, and articles devoted to the study of the kinetics of processes in which chemical transformations are either not decisive or absent altogether.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…With some degree of conventionality, it is possible to subdivide the articles published here into two main groups, namely, articles devoted to the study of the kinetics of processes in which any chemical transformations are decisive, and articles devoted to the study of the kinetics of processes in which chemical transformations are either not decisive or absent altogether. Among the articles of the first group, in turn, two categories can be distinguished, in the first of which are the clear majority; the processes related to them were considered in the articles [ 29 , 30 , 31 , 32 , 33 , 35 , 37 , 42 , 43 , 44 , 45 , 46 , 47 ]. For example, in [ 29 ], the kinetics of the aldol condensation of benzaldehyde and heptanal in liquid-phase systems using various solvents was characterized, and a very pronounced effect of the solvent was noted for a given set of identical kinetic parameters (i.e., the same kinetics of the liquid phase can lead to different values of conversion and yield of reaction products depending on the choice of solvent).…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Further attempts have been done by incorporation in LMPs of a series of additives including sucrose stearate, cholesterol, neutral lipids and charged phospholipids. [28][29][30][31][32][33][34][35] Inspired by these approaches, within this work 1, 2-dioleoylsn-glycero-3-phospho-(1 0 -rac-glycerol) (DOPG), 1,2-dioleoyl-snglycero-3-phospho-l-serine (DOPS) and 1, 2-dioleoyl-3-trimethylammonium propane (DOTAP) were added together with cholesterol (Chol) to a monoolein/water system to form a stable ultra-swollen cubic phase able to host and release a big macro molecule without disrupting the 3D structure of the gel. Small angle X-ray scattering (SAXS) and release experiments were used to elucidate how the size of the water channel, the phase identity of the gel and the electrostatic interaction between lipids and protein can be varied to achieve a tunable cargo release.…”
Section: Introductionmentioning
confidence: 99%